Agritourism in the Bug Valley in the Masovian Voivodeship - Katarzyna Radwańska; Dominik Dąbrowski; Janusz Leszek Sokół (Rozprawy Społeczne)
Abstract The paper presents forms of recreation undertaken in the rural areas of the Bug River communes of the Mazowieckie Voivodeship, as well as barriers and factors that favor agritourism and eco-tourism.